The Silent Epidemic-Chronic Pain and Palliative Care Needs in Children and Adolescents - Boris Zernikow (MDPI AG, 2024)
As the Section Editor-in-Chief, it is my pleasure to introduce the new section of Children dedicated to pediatric pain and palliative care [...]